2012
DOI: 10.4103/0974-1208.106335
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone supplementation in women with otherwise unexplained recurrent miscarriages

Abstract: CONTEXT:Recurrent miscarriages, the loss of three or more consecutive intrauterine pregnancies before 20 weeks of gestation with the same partner, affect 1%–1.5% of the pregnant population. The inadequate secretion of progesterone in early pregnancy has been proposed as a cause of recurrent miscarriages.AIMS:The aim was to investigate the efficacy of progesterone supplementation in patients with unexplained recurrent miscarriages.SETTINGS AND DESIGN:This was a 9-year cohort study of women with otherwise unexpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Indeed, as expected, 116 implantation rate after PBMC immunotherapy was over double compared to control 117 (24% vs 10%; table 2) and the result was similar to other studies with interval 21-25% 118 for treated patients [22-24, 26, 27]. 119 Nevertheless, it was commonly accepted that with insufficient P4 production causing 120 miscarriages could be solved simply by an exogenous P4 administration in order to 121 regulate the inflammatory mediators of pregnancy and even for patients undergoing IVF 122 process in fresh or frozen cycles to improve clinical outcomes prior embryo 123 transfer [29,35,36]. Indeed, P4 presents an anti-inflammatory action enhancing Th2 124 cytokines production to maintain pregnancy [37,38].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Indeed, as expected, 116 implantation rate after PBMC immunotherapy was over double compared to control 117 (24% vs 10%; table 2) and the result was similar to other studies with interval 21-25% 118 for treated patients [22-24, 26, 27]. 119 Nevertheless, it was commonly accepted that with insufficient P4 production causing 120 miscarriages could be solved simply by an exogenous P4 administration in order to 121 regulate the inflammatory mediators of pregnancy and even for patients undergoing IVF 122 process in fresh or frozen cycles to improve clinical outcomes prior embryo 123 transfer [29,35,36]. Indeed, P4 presents an anti-inflammatory action enhancing Th2 124 cytokines production to maintain pregnancy [37,38].…”
supporting
confidence: 72%
“…Indeed, it is known that P4 is an indispensable 32 factor for endometrium decidualization and for early stage of clinical pregnancy to 33 prepare an adequate immune environment for fetus and low LPL results abnormal 34 ongoing pregnancy [18,19,[29][30][31][32]. 35 Forward, it is increasingly clear that embryo implantation is dependent in one side 36 on immune local mechanisms and in another side on endocrine mechanisms related to 37 luteal P4 synthesis while their interactive reaction is still kept into question for 38 pregnancy achievement. For this reason, while our previous work [22] was based on the 39 implementation of PBMC immunotherapy for RIF patients and proving its efficiency 40 tripling the clinical outcomes, the present work was more focused on demonstrating the 41 correlation between LPL and immunotherapy success highlighting the interactive 42 reaction between luteal P4 synthesis by CL and immune system.…”
Section: Introductionmentioning
confidence: 99%
“…She had a low 25‐hydroxycholecalciferol level of 10 ng/ml, low vitamin B12 level of 190 picomol/ml. At the time, there was indirect evidence that low dose aspirin and prophylactic doses of low molecular weight heparin could increase the number of live births in women with recurrent miscarriages (Jain et al, ) and progesterone could prevent miscarriage (Hussain et al, ). Therefore, vitamin D, B 12 , progesterone, thyroid hormone replacement, folic acid, aspirin, and lovenox were given during every one of her pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The luteal blood flow increases gradually after ovulation, and the corpus luteum becomes one of the most highly vascularized organs in the body [7]. Previous studies have found that insufficiency of the corpus luteum during pregnancy was associated with infertility and spontaneous abortion in the first trimester of pregnancy [8,9]. In addition, blood flow in the corpus luteum is associated with luteal function.…”
Section: Introductionmentioning
confidence: 99%